Utilization of Social Media for Learning and Development of Livestock Business - Arlena, Wenny Maya; Muljono, Pudji; Sarwoprasodjo, Sarwititi; Herawati, Tin (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
One of the most significant innovations in the current digital era is the emergence of social media as a multifunctional platform that can be utilized for various needs, from communication between individuals to global collaboration, entertainment in multiple formats, digital content-based education, and business development and promotion in different sectors. Social media such as YouTube has proliferated into a platform that provides information that is easily accessible to multiple groups and has a significant positive impact. One of the impacts is the ease and speed of long-distance communication, which facilitates interaction between individuals or groups even though they are separated by space and time. This study aims to analyze the use of social media in learning and developing livestock businesses. The approach used in this study is descriptive qualitative, which adopts a constructivist paradigm and a case study approach. Two informants involved in this study were selected purposively because they have businesses in the livestock sector, especially goats. The results of the survey show that YouTube has proven to be an essential tool for farmers in improving business skills and efficiency because it provides easy access to practical knowledge about livestock management, such as feeding techniques, livestock health care, business management strategies, and independent learning resources, gaining knowledge from experts and experienced practitioners.